The Effects of Increment Taxes Upon Building Operations - Haig, Robert Murray (Quarterly Journal of Economics, 1915)
Journal Article The Effects of Increment Taxes upon Building Operations Get access Robert Murray Haig Robert Murray Haig Columbia University Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 29, Issue 4, August 1915, Pages 829–840, https://doi.org/10.2307/1883311 Published: 01 August 1915